The interdependence of stock market among Malaysia and selected Middle East countries: analysis based on conventional and Islamic Stock Index / Erlie Sharina Kamisan - Kamisan, Erlie Sharina (Faculty of Business and Management, 2015)
The aim of this study is to investigate the level of international equity market interdependence among Malaysia and selected Middle East country (Jordan, United Arab Emirates, Bahrain and Qatar) for Islamic and conventional stock index. The daily closing price of stock indices is collected from 1st January 2010 until 1st January 2015. From the result, it reveals that Jordan conventional stock index and Qatar conventional stock index have strong association. For Islamic stock index, UAE Islamic stock index and Qatar Islamic stock index have strong association. Besides, UAE Islamic stock index and Bahrain Islamic stock index shows strong association. However, Bahrain conventional and Islamic stock exchange is the least stock market that associate with Malaysia and Middle East conventional and Islamic stock market. Findings reveal that there is weak correlation between Malaysia and selected Middle East conventional and Islamic stock markets during period from 1st January 2010 until 1st January. In terms of relationship, Qatar conventional stock exchange shows strong bidirectional relationship to Malaysia and selected Middle East countries. Meanwhile, Bahrain conventional stock exchange do not have any significant relationship with Malaysia, Jordan and Qatar conventional stock exchange. Result also reveal UAE Islamic stock index have strong bidirectional relationship to Malaysia and selected Middle East countries. However, Jordan Islamic stock index do not have any significant relationship with Malaysia, Bahrain and Qatar Islamic stock exchange. Overall findings conclude that there is no differences between international market interdependence of Islamic and Conventional among Malaysia and selected Middle East countries.